2014
DOI: 10.3892/ijo.2014.2772
|View full text |Cite
|
Sign up to set email alerts
|

Pien Tze Huang inhibits metastasis of human colorectal carcinoma cells via modulation of TGF-β1/ZEB/miR-200 signaling network

Abstract: Tumor metastasis, a complex process involving the spread of malignant tumor cells from a primary tumor site to a distant organ, is a major cause of failure of cancer chemotherapy. Epithelial-mesenchymal transition (EMT) is a critical step for the initiation of cancer metastasis. The processes of EMT and metastasis are highly regulated by a double-negative feedback loop consisting of TGF-β1/ZEB pathway and miR-200 family, which therefore has become a promising target for cancer chemotherapy. Pien Tze Huang (PZH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
(61 reference statements)
1
28
0
Order By: Relevance
“…The TCM treatment of cancer has received widespread attention due to its therapeutic efficacy and relatively few side effects. Previous studies have demonstrated that the commonly used TCM formula PZH can inhibit the growth and metastasis of colorectal cancer cells (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, its effects on HCC and the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCM treatment of cancer has received widespread attention due to its therapeutic efficacy and relatively few side effects. Previous studies have demonstrated that the commonly used TCM formula PZH can inhibit the growth and metastasis of colorectal cancer cells (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, its effects on HCC and the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Pien Tze Huang (PZH), a well-known TCM formula that originated in the Chinese Ming Dynasty >450 years ago, has been widely used in China and Southeast Asia as a remedy for various diseases, including cancer (36). It was previously demonstrated that PZH may inhibit colon cancer growth via multiple mechanisms (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) and PZH has exhibited promising therapeutic effects in clinical trials regarding HCC (50,51). However, the effect of PZH on HCC, including on miR-16 expression level, has not been evaluated; therefore, the present study aimed to explore the effect of PZH on the proliferation and apoptosis of the HCC BEL-7402 cell line.…”
Section: Introductionmentioning
confidence: 99%
“…PZH, as a TCM formula, has been demonstrated to have cancer activity via a number of mechanisms, including the stimulation of apoptosis, inhibition of proliferation and regulati multiple downstream cancer-related signaling molecules in CRC cells. Previous studies have identified that PZH can regulate a number of miRNAs, such as the miR-200 family (19).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metastasis is a complex process, and is highly regulated by multiple mechanisms, including aberrant activation of the phosphoinositide 3-kinase (PI3K)/AKT and transforming growth factor (TGF)-β/Smad pathways (8)(9)(10)(11). Furthermore, a large number of studies have shown that matrix metalloproteinase (MMP) overexpression is involved in numerous malignant tumors, including esophageal cancer, breast cancer, liver cancer and rectal cancer (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%